PENINGKATAN KEMAMPUAN MENULIS PARAGRAF DESKRIPSI RAGAM KRAMA MELALUI METODE PEMODELAN DAN MEDIA GAMBAR TEMATIK PADA SISWA KELAS X IIS 2 SMA - Anggraeni P, Prihatiningrum Ikha; Rahadini, Astiana Ajeng; Sumarwati, Sumarwati (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2019)
The objectives of this research are to increase the quality of learning process in writing paragraph description diversion of krama and students’ paragraph description diversion of krama writing skill result through implementing modeling method and tematical images to X Social Science 2 students of SMA Negeri 3 Boyolali. This research is a classroom action research (CAR) with 2 cycles. Each cycle contains of 4 stages, namely; action plan, conduct action, observation and interpretation, and also analysis and reflection. Subject of this research are the students of X Social Science 2 of SMA N 3 Boyolali which contains of 36 students. The data collection techiques are observation, interview, and test. Validity data test use triangulation method and triangulation data souce. Data analysis techniques are descriptiv comparative and critical analysis. The result of this research indicate that the implementation of make a match model and macromedia unity can increase the quality of  learning process in writing paragraph description  and students’ paragraph description  writing skill result to X Social Science 2 students of SMA N 3 Boyolali. The result can be proven since preaction until cycle 2 in preaction, the average of learning qualiti is about 71. Then in cycle I learning quality becomes 75, and in the end of cycle II it increase becomes 80 or in other words it is a good category. Quality of students writing wangsalan skill also indicate an improve ment, in preaction students who get minimum standard score is about 44,44%, then in cycle I it becomes 77,78% and in the end of cycle 2 becomes 89%.